Genotyping-by-Sequencing Uncovers the Introgression Alien Segments Associated with Sclerotinia Basal Stalk Rot Resistance from Wild Species—I. Helianthus argophyllus and H. petiolaris - Qi, Lili; Long, Yunming; Talukder, Zahirul I.; Seiler, Gerald J.; Block, Charles C.; Gulya, Thomas J. (Frontiers in Genetics, 2016)
Basal stalk rot (BSR), caused by Sclerotinia Sclerotiorum, is a devastating disease in sunflower worldwide. The progress of breeding for Sclerotinia BSR resistance has been hampered due to the lack of effective sources of resistance for cultivated sunflower. Our objective was to transfer BSR resistance from wild annual Helianthus species into cultivated sunflower and identify the introgressed alien segments associated with BSR resistance using a genotyping-by-sequencing (GBS) approach. The initial crosses were made between the nuclear male sterile HA 89 with the BSR resistant plants selected from wild Helianthus argophyllus and H. petiolaris populations in 2009. The selected resistant F1 plants were backcrossed to HA 458 and HA 89, respectively. Early generation evaluations of BSR resistance were conducted in the greenhouse, while the BC2F3 and subsequent generations were evaluated in the inoculated field nurseries. Eight introgression lines; six from H. argophyllus (H.arg 1 to H.arg 6), and two from H. petiolaris (H.pet 1 and H.pet 2), were selected. These lines consistently showed high levels of BSR resistance across seven environments from 2012 to 2015 in North Dakota and Minnesota, USA. The mean BSR disease incidence (DI) for H.arg 1 to H.arg 6, H.pet 1, and H.pet 2 was 3.0, 3.2, 0.8, 7.2, 7.7, 1.9, 2.5, and 4.4%, compared to a mean DI of 36.1% for Cargill 270 (susceptible hybrid), 31.0% for HA 89 (recurrent parent), 19.5% for HA 441 (resistant inbred), and 11.6% for Croplan 305 (resistant hybrid). Genotyping of the highly BSR resistant introgression lines using genotyping-by-sequencing revealed the presence of the H. argophyllus segments in linkage groups (LGs) 3, 8, 9, 10, and 11 of the sunflower genome, and the H. petiolaris segments only in LG8. The shared polymorphic SNP loci in the introgression lines were detected in LGs 8, 9, 10, and 11, indicating the common introgression regions potentially associated with BSR resistance. Additionally, a downy mildew resistance gene, Pl17, derived from one of the parents, HA 458, was integrated into five introgression lines. Germplasms combining resistance to Sclerotinia BSR and downy mildew represent a valuable genetic source for sunflower breeding to combat these two destructive diseases.